Crises and resilience in family firms - Casprini, Elena; Conz, Elisa; Murphy, Linda; Zanni, Lorenzo; Zucchella, Antonella (Piccola Impresa / Small Business, 2023)
Purpose: In this editorial, the Guest Editors introduce the key themes of the Special Issue “Crises and resilience in family firms”. The five papers here presented provide theoretical and empirical contributions to the family business field, by analysing resilience in the context of the pandemic Covid-19. Specifically, resilience is explored at the firm level through the lenses of entrepreneurship, strategic management, and innovation management literature. Findings: Authors illustrate how family businesses managed the changes brought by the unexpected spread of the pandemic and underline how the specificities of family firms, like the preservation of SEW, a purpose driven orientation, the routinized capacity of being resilient, the care of customer relationships, the individual resilience of the entrepreneur and the specific female characteristics of successor represent a key competitive advantage of family businesses, especially if female-driven, over non-family firms.